MOLECULAR CHARACTERIZATION OF LASIODIPLODIA THEOBROMAE ASSOCIATED WITH CITRUS GUMMOSIS FROM MAJOR CITRUS GROWING AREAS OF PUNJAB, PAKISTAN - M. Z. Ahmed; L. Amrao; M. A. Ali; Z. Ul Abdin (Journal of Animal and Plant Sciences, 2019)
The worldwide extension of cultivation areas of citrus has contributed to the emergence of various diseases. Gummosis is one of the most significant diseases of citrus. The disease is caused by several species of Botryosphaeriacae, the most prominent ones are Lasiodiplodia spp.  The objective of this study was molecular identification and characterization of Lasiodiplodia theobromae associated with citrus gummosis from major citrus growing areas of Punjab, Pakistan. This study includes activities like collection of diseased samples, isolation, morphological identification, molecular characterization and pathogenicity of L. theobromae on citrus bark tissues. To identify the cause of citrus gummosis disease, symptomatic diseased bark tissues were collected from 30 localities of 5 cities of the province Punjab. L. theobromae was isolated from all the infected samples. Preliminary identification was based on morphological and cultural characters of isolated fungi. For molecular studies nucleotide sequences of the ITS region (ITS1-5.8S-ITS2) was used. For pathogenicity analysis all identified isolates of L. theobromae inoculated on Citrus jambhiri which is commonly used as rootstock in Punjab. Isolates of L. theobromae produced typical symptoms of citrus gummosis and significant difference in virulence was found. Our data confirms the association of L. theobromae with citrus gummosis in Punjab, Pakistan. No other genus of Botryosphaeriacae except Lasiodiplodia was found to be associated with this disease. This preliminary research work opens new frontiers for the development of sustainable management strategies for the control of gummosis disease in citrus orchards.
Keywords: Citrus; Gummosis; Lasiodiplodia theobromae; Punjab; rDNA-ITS